Erratum: Upaya Peningkatan Hasil Belajar Bola Basket Menggunakan Model Pembelajaran Group Investigation - Abdul Hanansyah; Agi Ginanjar (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.543 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.